2015
DOI: 10.1021/jacs.5b02879
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Cations with Exceptional Alkaline Stability: A Systematic Study of Structure–Stability Relationships

Abstract: Highly base-stable cationic moieties are a critical component of anion exchange membranes (AEMs) in alkaline fuel cells (AFCs); however, the commonly employed organic cations have limited alkaline stability. To address this problem, we synthesized and characterized the stability of a series of imidazolium cations in 1, 2, or 5 M KOH/CD3OH at 80 °C, systematically evaluating the impact of substitution on chemical stability. The substituent identity at each position of the imidazolium ring has a dramatic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
418
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(440 citation statements)
references
References 164 publications
(47 reference statements)
17
418
1
1
Order By: Relevance
“…In the intensive search for cations with high alkaline stability, certain heterocycloaliphatic QA cations 15 and sterically hindered imidazolium cations [22][23][24] have been reported to possess outstanding alkaline stability. For example, N,N-dimethylpiperidinium and 6-azonia-spiro [5.5]undecane-6-ium cations show approximately 21 and 26 times longer halimes, respectively, than the conventional benzyltrimethyl QA cation in 6 M NaOH at 160 C. 15 The high stability of the former cations has been ascribed to low ring strain and to constrained conformations imposed by the ring structure, which increase the transition state energy of both substitution and elimination reactions.…”
Section: -21mentioning
confidence: 99%
“…In the intensive search for cations with high alkaline stability, certain heterocycloaliphatic QA cations 15 and sterically hindered imidazolium cations [22][23][24] have been reported to possess outstanding alkaline stability. For example, N,N-dimethylpiperidinium and 6-azonia-spiro [5.5]undecane-6-ium cations show approximately 21 and 26 times longer halimes, respectively, than the conventional benzyltrimethyl QA cation in 6 M NaOH at 160 C. 15 The high stability of the former cations has been ascribed to low ring strain and to constrained conformations imposed by the ring structure, which increase the transition state energy of both substitution and elimination reactions.…”
Section: -21mentioning
confidence: 99%
“…Both the small molecule and the analogously structured polymer were found to be stable for extended periods in 2 m KOH aq at 60 8 8C. [18] To date,o nly three polymers have been reported that utilize this type of C2protection strategy for (benz)imidazoliums, [3,16,19] yet it provides the most likely strategy towards alkaline-stable,h ydroxide-conducting polymers.The discovery that o-dimethylphenylenes can protect the C2 position opens the door to other o-substituted phenylene variants,s uch as halogen or aryl protecting groups. The stability of these molecules was supported by density functional theory (DFT) calculations of Long and Pivovar, showing that methyl protecting groups greatly enhance the stability of imidazolium and benzimidazolium hydroxides over that of quaternary ammoniums.…”
mentioning
confidence: 99%
“…New cation structures by Yan, et al, and others have energized the field in the search for novel cations and greatly expanded the pallet of possibilities. [33][34][35][36][37][38][39][40] However, many new types of cations have not been validated across a number of independent groups in materials or devices. Additionally, many novel cations can be expensive.…”
Section: Strategies For Developing New Anion Exchange Membranes and Ementioning
confidence: 99%
“…So far, the field has approached AEM stability by examining the nucleophilic or hydroxide resistance of the materials. Degradation studies employing modeling, 57 small molecules, 36,41,58 and polymers 31,35 have all contributed to a growing body of work outlining the most hydroxide resistant building blocks for these materials. However, the mechanisms operating in high reactivity hydroxide environments may not be representative of what is occurring in an electrochemical device-especially in regard to oxidative stress and not fully hydrated conditions (e.g., low humidity).…”
Section: Perspective and Conclusionmentioning
confidence: 99%